Dabrafenib and Trametinib in BRAF Mutant Metastatic Conjunctival Melanoma - Rossi, Ernesto; Maiorano, Brigida Anna; Pagliara, Monica Maria; Sammarco, Maria Grazia; Dosa, Tommaso; Martini, Maurizio; Rindi, Guido; Bria, Emilio; Blasi, Maria Antonietta; Tortora, Giampaolo; Schinzari, Giovanni (Frontiers in Oncology, 2019)
Conjunctival melanoma is a rare primary ocular tumor. So far, no standard treatment exhists for metastatic disease. Similarly to cutaneous melanoma, up to 50% of conjunctival melanomas harbor BRAF mutations. The most common is represented by V600E. Combined therapy with BRAF and MEK inhibitors is approved for BRAF mutant cutaneous metastatic melanomas. Herein, we report a case of a 70-years old patient with a metastatic conjunctival melanoma harboring V600E BRAF mutation succesfully treated with dabrafenib and trametinib.